2018
DOI: 10.1186/s12544-018-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

Transport indicator analysis and comparison of 151 urban areas, based on open source data

Abstract: Introduction: The accurate analysis and comparison of transport indicators from a large variety of urban areas can help to evaluate the performance of different adopted transport policies. This paper attempts to determine important transport and socioeconomic indicators from 151 urban areas and 51 countries, based on comparable, directly observable open-source data such as OpenstreetMap (OSM) and the TomTom database. Analysis: This is the first, systematic indicator-analysis using recent, open source data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
(30 reference statements)
4
29
0
1
Order By: Relevance
“…Some studies have also shown that an increase in alternative transport systems' infrastructure alleviates traffic road congestion. This effect has been demonstrated in [25,26] for rail transit systems, in [27,28] for public transportation in general and in [25] for cycling. These results suggest that the IA, in terms of infrastructure per capita, is an important factor for determining the usage of transportation systems.…”
Section: Relationship Between Infrastructure Dynamics and Transport Pmentioning
confidence: 89%
See 3 more Smart Citations
“…Some studies have also shown that an increase in alternative transport systems' infrastructure alleviates traffic road congestion. This effect has been demonstrated in [25,26] for rail transit systems, in [27,28] for public transportation in general and in [25] for cycling. These results suggest that the IA, in terms of infrastructure per capita, is an important factor for determining the usage of transportation systems.…”
Section: Relationship Between Infrastructure Dynamics and Transport Pmentioning
confidence: 89%
“…A number of studies have found that an increase in road infrastructure increases car ownership and usage [20][21][22] and an increase in rail network infrastructure increases rail mode share, resulting from a modal shifts from car to public transport [22-]. It has been demonstrated that an increase in demand rises the travel delay time, while an increase in IA (as road length per inhabitant) decreases the travel delay time [25]. Some studies have also shown that an increase in alternative transport systems' infrastructure alleviates traffic road congestion.…”
Section: Relationship Between Infrastructure Dynamics and Transport Pmentioning
confidence: 99%
See 2 more Smart Citations
“…This has contributed to an unsustainable mobility model that is excessively dependent on private car use [2]. Predictably, Flemish roads are also among the most congested in Europe [3,4]. Urban sprawl and road congestion contribute significantly to negative environmental and health impacts [5,6], greenhouse gas emission [7], landscape and ecosystem degradation [8][9][10] and economic losses [3,11].…”
Section: Introductionmentioning
confidence: 99%